β2-Microglobulin amyloid fibril-induced membrane disruption is enhanced by endosomal lipids and acidic pH. - Sophia C Goodchild; Tania Sheynis; Rebecca Thompson; Kevin W Tipping; Wei-Feng Xue; Neil A Ranson; Paul A Beales; Eric W Hewitt; Sheena E Radford (PLoS ONE)
Although the molecular mechanisms underlying the pathology of amyloidoses are not well understood, the interaction between amyloid proteins and cell membranes is thought to play a role in several amyloid diseases. Amyloid fibrils of β2-microglobulin (β2m), associated with dialysis-related amyloidosis (DRA), have been shown to cause disruption of anionic lipid bilayers in vitro. However, the effect of lipid composition and the chemical environment in which β2m-lipid interactions occur have not been investigated previously. Here we examine membrane damage resulting from the interaction of β2m monomers and fibrils with lipid bilayers. Using dye release, tryptophan fluorescence quenching and fluorescence confocal microscopy assays we investigate the effect of anionic lipid composition and pH on the susceptibility of liposomes to fibril-induced membrane damage. We show that β2m fibril-induced membrane disruption is modulated by anionic lipid composition and is enhanced by acidic pH. Most strikingly, the greatest degree of membrane disruption is observed for liposomes containing bis(monoacylglycero)phosphate (BMP) at acidic pH, conditions likely to reflect those encountered in the endocytic pathway. The results suggest that the interaction between β2m fibrils and membranes of endosomal origin may play a role in the molecular mechanism of β2m amyloid-associated osteoarticular tissue destruction in DRA.